Arteriovenous malformations of the head and neck: current concepts in management. Issue 5 (June 2016) - Fowell, Christopher; Jones, Robert; Nishikawa, Hiroshi; Monaghan, Andrew
Abstract: The field of vascular anomalies and their clinical management is expanding and developments in the last few years have improved the understanding of haemangiomas and vascular malformations. In this paper, the first in the series of 3 educational reviews, we review the current trends and evidence-based management of arteriovenous malformations.